G Gambaran Tingkat Kecemasan Masyarakat Pasca Banjir di Desa X - Muhammad Najmi; Muthmainnah Muthmainnah (Journal of Nursing Invention, 2022)
Background: Flood is the most frequent disaster in Indonesia. The impacts that occur as a result of this flood disaster include damage to infrastructure, facilities and infrastructure, the economy, emotional disturbance and even to the loss of human life. One of the most common emotional disturbances is anxiety. Anxiety is a natural disorder of feelings that arises with a feeling of worry, fear that is sustainable and deep. Objective: Knowing the level of anxiety of the post-flood community in Village x Method: This study uses a quantitative method, with a descriptive approach and uses a cross sectional approach. The population in this study were all the people in Village X who were affected by the flood, namely 612. The sampling technique in this study used a simple random sampling technique with a total sample of 86 people. Results: The results of the study found that the village community x had a mild level of anxiety. Conclusion: the level of anxiety of the people in the village x in 2022 will experience the most mild anxiety. It is also hoped that the results of this study can provide additional insight and knowledge related to disaster nursing and this research can help researchers and future researchers to determine the level of anxiety of the post-flood community